Understanding Supply Chain Risk: A Self-Assessment Workbook - (:unkn) unknown (Cranfield University School of Management, 2003)
The events of the last few years from the fuel crisis to foot and mouth disease to port blockades and SARS have highlighted the vulnerability of many supply chains. There are many forms of supply chain risk - internal to the company and external - that can impact a company’s ability to maintain its operations and to serve its customers. Recognising the implications for the economy and in particular small and medium enterprises (SMEs) the Department for Transport initiated a research programme into supply chain vulnerability. The research, undertaken by the Cranfield Centre for Logistics and Supply Chain Management revealed that there is still a lack of understanding, and assessment, of supply chain risks. During the research it became evident that there was a need to provide a simple approach to enable managers to assess supply chain risk. This Workbook will, we hope, meet that need.